2016
DOI: 10.1128/jvi.01522-16
|View full text |Cite
|
Sign up to set email alerts
|

Adoptive Transfer of Engineered Rhesus Simian Immunodeficiency Virus-Specific CD8+T Cells Reduces the Number of Transmitted/Founder Viruses Established in Rhesus Macaques

Abstract: AIDS virus infections are rarely controlled by cell-mediated immunity, in part due to viral immune evasion and immunodeficiency resulting from CD4؉ T-cell infection. One likely aspect of this failure is that antiviral cellular immune responses are either absent or present at low levels during the initial establishment of infection. To test whether an extensive, timely, and effective response could reduce the establishment of infection from a high-dose inoculum, we adoptively transferred large numbers of T cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 55 publications
(80 reference statements)
3
23
0
Order By: Relevance
“…Other adoptive transfer studies relying on longer, more extensive in vitro selection and expansion of naturally occurring SIV-specific T-cell clones in culture rather than the limited ex vivo expansion made possible by engineering T cells presented here have observed no detectable persistence in either blood or tissues other than the lung (47,48). Recently, we applied T-cell engineering techniques to express CCR7/CD62L on T cells and observed limited, but unequivocal trafficking to lymph nodes and avoidance of the lung, demonstrating targeting of infused T cells to lymphoid tissues in a nonhuman primate system (43). Here, we extend this concept with cells that had less extensive expansion ex vivo than used in our prior CCR7/CD62L study, and we observed greater frequencies of infused cells in the secondary lymphoid tissues.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Other adoptive transfer studies relying on longer, more extensive in vitro selection and expansion of naturally occurring SIV-specific T-cell clones in culture rather than the limited ex vivo expansion made possible by engineering T cells presented here have observed no detectable persistence in either blood or tissues other than the lung (47,48). Recently, we applied T-cell engineering techniques to express CCR7/CD62L on T cells and observed limited, but unequivocal trafficking to lymph nodes and avoidance of the lung, demonstrating targeting of infused T cells to lymphoid tissues in a nonhuman primate system (43). Here, we extend this concept with cells that had less extensive expansion ex vivo than used in our prior CCR7/CD62L study, and we observed greater frequencies of infused cells in the secondary lymphoid tissues.…”
Section: Discussionmentioning
confidence: 81%
“…The frequencies of the infused T cells in PBMC from necropsy samples were decreased approximately 10-fold from those of the 15-min postinfusion samples, ranging from 0.3 to 1% (n ϭ 6; x ϭ 0.7%; SD ϭ 0.25%), suggesting movement of the infused cells out of the peripheral circulatory system. One common observation in adoptive transfer studies is that bronchoalveolar lavage sampling of animals contain high frequencies of infused cells, presumed to be "trapped" in the lung (43,47,48). Flow cytometry of CD3 ϩ cells isolated from the prenecropsy bronchoalveolar lavage samples showed a high frequency of infused cells relative to the endog- enous T cells, from 7 to 76% (n ϭ 6; x ϭ 54%; SD ϭ 24%) consistent with retention of some of the infused cells in the lung.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Meanwhile, experiments designed to change the numbers of CD8+ T cells in circulation have an important (but variable) impact on viral load. These include experiments to increase the number of CD8+ T cells, such as infusion of these cells [18][19][20][21][22][23][24] and studies of vaccines leading to large expansions of the circulating CD8+ T-cell counts. 25,26 The opposite approach, trying to reduce CD8+ cells, by infusion of depleting antibodies, has also been attempted in simian immunodeficiency virus (SIV) animal models, usually leading to significant increases in viral load.…”
Section: Cells 11mentioning
confidence: 99%
“…Indeed, mounting evidence suggests that lentivirus-specific CD8 ϩ T cells can do more than reduce viremia in productively infected individuals. For instance, a recent study has shown that adoptively transferring large quantities of SIV-specific CD8 ϩ T cells into RMs 3 days after a high-dose IR challenge with SIV can reduce the number of transmitted/founder viruses in infected animals (56). Although this approach did not prevent the establishment of productive infection, it lends support to the notion that high frequencies of vaccine-elicited CD8 ϩ T cells situated at relevant sites of virus replication can intercept a nascent infection before it becomes systemic.…”
Section: Discussionmentioning
confidence: 99%